To breastfeed or not to breastfeed? Lack of evidence on the presence of SARS-CoV-2 in breastmilk of pregnant women with COVID-19 - Paulo Ricardo Martins-Filho; Victor Santana Santos; Hudson P. Santos Jr (Pan American Health Organization, 2020)
A rapid systematic review was carried out to evaluate the current evidence related to the presence of SARSCoV-2 in breast milk from pregnant women with COVID-19. Eight studies analyzing the presence of SARS-CoV-2 RNA in the breast milk of 24 pregnant women with COVID-19 during the third trimester of pregnancy were found. All patients had fever and/or symptoms of acute respiratory illness and chest computed tomography images indicative of COVID-19 pneumonia. Most pregnant women had cesarean delivery (91.7%) and two neonates had low birthweight (< 2 500 g). Biological samples collected immediately after birth from upper respiratory tract (throat or nasopharyngeal) of neonates and placental tissues showed negative results for the presence SARS-CoV-2 by RT-PCR test. No breast milk samples were positive for SARS-CoV-2 and, to date, there is no evidence on the presence of SARS-CoV-2 in breast milk of pregnant women with COVID-19. However, data are still limited and breastfeeding of women with COVID-19 remains a controversial issue. There are no restrictions on the use of milk from a human breast milk bank.